تحليل الشعر "زهر اللوز او أبعد" لمحمود درويش الدرسة السيمائية ريفاتير - Munawarah, Nisaul (Journal of Arabic Language and Literature (ALLAIS), 2022)
The problem in this research is the hidden meaning contained in Mahmoud Darwish's collection of poems entitled Almon Yang Blooms and Other Things. This study aims to describe (1) heuristic and hermeneutic readings, (2) matrices, models, and variants in Mahmoud Darwish's collection of poems entitled Almon Yang Mekar and other things on the theme "Aku". Based on the data sources studied, the researchers found signs that indirectly have meaning. The results of heuristic readings on each title in the theme of "I" show that this poem tells about the poet's feelings in facing the war that occurred in his country which is expressed through several seasons such as autumn, spring, and winter. Then the poet's hermeneutic reading has a hope in his country that is not necessarily achieved. The matrix on the theme of "I" is a poet who hopes for happiness in the midst of war. The model for the “I” theme is Blooming Almonds. The model is transformed into variants, namely variants I, II, III.